Pengaruh CAR, BOPO, ROA dan BI RATE terhadap NPL Bank - Adriella Resmita Sunny Pardosi; Francis Hutabarat; Harlyn Siagian (IPM2KPE, 2024)
This research aims to evaluate the impact of Capital Adequacy Ratio (CAR), Operational Expenses on Operating Income (BOPO), Return on Assets (ROA), and BI Rate on Non-Performing Loans (NPL) of Banks in Indonesia from 2019 to 2021. Method used is panel regression analysis with data from the financial reports of 43 banks published by the Financial Services Authority (OJK). The sample includes banks that are listed on the Indonesian Stock Exchange and have complete data for that period. The research results show that CAR does not have a significant influence on bank NPL, indicating that the availability of bank capital does not significantly influence the level of bank non-performing loans. On the other hand, BOPO has an effect on bank NPLs, where high operational costs and low operating income tend to increase the bank's level of non-performing loans. ROA also does not have a significant effect on bank NPL, indicating that the rate of return on bank assets does not substantially influence the level of bank non-performing loans. However, the BI Rate has a significant influence on bank NPLs, indicating that Bank Indonesia's benchmark interest rate (BI Rate) has a significant impact on the level of bank non-performing loans. In conclusion, the research emphasizes the importance of managing operational efficiency and paying attention to changes in the BI Rate to control credit risk and maintain a healthy NPL level. Keywords: CAR, BOPO, BI RATE, NPL, ROA